Kajian Naratif : Analisis Pengadaan Obat Sebelum Dan Selama Pandemi (COVID-19) - Sonia Sonia; Tri Nurhayati Asih (Jurnal Sehat Masada, 2024)
Pandemic problems cause life to shift especially in the health services side. The need for drugs and other medical products is overwhelming. Increased need is not coupled with availability of possessions. The health unit needs to adjust the planning and management of the logistics of medicines in the healthcare unit. To that end, the study deals with changes and problems that occurred during the pandemic of drug planning and procuring logistics for future evaluation.The goal of the riview literature is to know how the planning and procuring of drugs before and during the pandemic (covid-19)..This research method did so with literature review obtained from the national and international journals of the last five years from Google scholar, and digital.The discussion discussed how the initial step of planning takes place until it reaches a mature plan. The stage of planning is followed by procurement. Its procurement during the pandemic is changing interpretations of its logical mechanism. This assessment presents a discussion of how the change of interpretation occurred during the pandemic. Drug planning is the basis for the implementation of the drug's logism-management mechanism. Careful planning makes it easier to procuring the drug without swelling in the budget, excess, and lack of medical supplies.